CORPORATE GOVERNANCE AND AUDIT REPORT TIMELINESS OF LISTED NON-FINANCIAL FIRMS IN NIGERIA (Journal of Global Accounting, 2024)
This study investigates the effect of corporate governance structure on audit report timeliness of listed non-financial firms in Nigeria. The main objective was to determine the effect of cooperative governance, proxied by (board size, board independence, board gender diversity and board diligence) on the audit report timeliness of listed non-financial firms in Nigeria. Ex-post facto research design was chosen for the study. Purposive sampling was used in selecting a sample size of fifty-four firms from a total population of seventy-four. Secondary data were collected from the annual reports of the selected firms over a ten-year period that covered 2014 to 2023. Analyses of data were done using preliminary tools such as descriptive statistics, test of heteroskedasticity, multicollinearity, cross-sectional dependence and Hausman specification test after which the hypotheses were tested using Panel Estimated Generalized Least Squares. The findings revealed that: board size has a significant positive effect on the audit report timeliness of listed non-financial firms in Nigeria (p-value = 0.0160); board independence has a significant positive effect on the audit report timeliness of listed non-financial firms in Nigeria (p-value = 0.0000); board gender diversity has a non-significant positive effect on the audit report timeliness of listed non-financial firms in Nigeria (p-value = 0.1870); board diligence has a non-significant positive effect on the audit report timeliness of listed non-financial firms in Nigeria (p-value = 0.1036). In conclusion, larger, more independent, and diverse boards, along with diligent governance practices, contribute to a robust oversight mechanism that facilitates timely audit reporting. Diverse boards that include a mix of genders are likely to benefit from varied perspectives and approaches to problem-solving, which can improve the overall effectiveness of governance practices. Gender-diverse boards may also exhibit higher levels of diligence and ethical standards, fostering a culture that values transparency and accountability. Finally, diligent boards that meet regularly and are actively involved in governance are better positioned to monitor the progress of the audit process closely. The study therefore recommends that the Board Chairperson should foster a culture of diligence by increasing the frequency and thoroughness of board meetings to ensure proactive oversight and timely completion of the audit process
Keywords: Audit Report; Audit report timeliness; Board of Directors; Board Diligence; Board Gender Diversity, Board Independence; Board Size; Corporate Governance Attributes; Corporate Governance; Non-Financial Firms